High-Dose Ashwagandha Extract: A Toxicological Assessment in Male Wistar Rats Using a Dose-Dependent Approach - Gad, Enas Sayed; Buobaid, Afnan Omar; ALfraih, Aisha Yousef; Alanazi, Graham Mohammed; Alrashid, Mariyayah Abdullah; Alessa, Maisaa Ibrahim; Alduhayyan, Nora Adel; Aldossari, Rasha Naser (Indian Journal of Pharmaceutical Education and Research)
Background/Aim: The rising utilization of Ashwagandha (Withania somnifera), a well-known adaptogen and herbal supplement, has prompted apprehensions over its safety at elevated dosages. This study examines the potential hazardous consequences of different high dosages of Ashwagandha, seeking to elucidate its safety profile at elevated concentrations. Materials and Methods: Over 30 days, four groups of laboratory animals (male rats) were given varying high dosages of Ashwagandha root extract (2000 mg to 5000 mg per day). The groups were divided as follows: (1) Control group: administered a single oral dose of saline (15 mL/kg, once daily), (2) Diseased group (2000): administered a single oral dose of Ashwagandha (2000 mg/kg, once daily), (3) Diseased group (3000): administered a single oral dose of Ashwagandha (3000 mg/kg, once daily), (4) Diseased group (5000): administered a single oral dose of Ashwagandha (5000 mg/kg, once daily). Upon completion of the trial, scarification was performed on all rats, followed by examining several toxicity biomarkers, including liver and kidney function and hematological parameters, utilizing colorimetric and ELISA kits. Furthermore, the histological evaluations of essential organs were also conducted. Results: Results demonstrated dose-dependent changes in hepatic enzyme activity, renal function, and cellular integrity, indicating that excessive consumption may have detrimental effects. These findings emphasize the necessity for prudent dosage recommendations and long-term clinical research to determine safe usage protocols for high-dose Ashwagandha supplementation. Conclusion: This study offers essential insights into the toxicological concerns linked to excessive Ashwagandha utilization. It highlights that doses up to 2000 mg/kg are deemed safe and exhibit no detrimental impacts on any of the organs assessed in the current research. Nevertheless, the elevated dosages of 3000 and 5000 mg/kg elicited hazardous effects on the evaluated organs.
Keywords: Ashwagandha; Roots; High doses; Rats; Organ Toxicity